2010
DOI: 10.1177/030089161009600505
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Upper Urothelial Carcinoma in an Area of Balkan Endemic Nephropathy in South Serbia. A fifty-year Retrospective Study

Abstract: An increased number of transitional cell carcinoma in endemic settlements was observed, markedly decreasing in the last decade. An increasing age and a shorter survival were recorded in patients both from Balkan endemic nephropathy and control settlements. Sporadic cases upper urinary tract transitional cell carcinoma in settlements adjacent to endemic settlements were demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
7
16
1
Order By: Relevance
“…A similar gender distribution also was noted in BEN patients with UUC . In contrast, UUC patients residing in non‐endemic villages in the Balkans were predominantly male . In our study, two‐thirds of AA‐UUC patients were female, while two‐thirds of non‐AA‐UUC patients were male.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A similar gender distribution also was noted in BEN patients with UUC . In contrast, UUC patients residing in non‐endemic villages in the Balkans were predominantly male . In our study, two‐thirds of AA‐UUC patients were female, while two‐thirds of non‐AA‐UUC patients were male.…”
Section: Discussionsupporting
confidence: 84%
“…However, the gender distribution of Taiwanese UUC patients was approximately equal . A similar gender distribution also was noted in BEN patients with UUC . In contrast, UUC patients residing in non‐endemic villages in the Balkans were predominantly male .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The incidence of UTUC in Western countries is relatively low (5% of all urothelial carcinoma); however, the prognosis of UTUC is considerably worse than that at the same pathological stage of urothelial carcinoma of the bladder (UCB) [1][2][3]. The incidence of UTUC in Taiwan is considerably higher than the worldwide incidence (30%-40% of all urothelial carcinoma cells (UCs)), which indicates that some unknown carcinogenic or environmental factors contribute to tumor development and growth [4][5][6][7]. Histologically, UCs arising from the upper urinary tract and urinary bladder are grossly identical.…”
Section: Introductionmentioning
confidence: 99%
“…In Chinese populations, the use of traditional Chinese medicine containing aristolochic acid (AA) might affect tumor multifocality, and a previous study of UTUC in Balkan endemic nephropathy patients indicated that malignancy was lower in UTUCs caused by AA [20]. Our previous research also suggests specific treatments that may be most effective for multiple or bilateral UTUC [21, 22], but choosing the best surgical approach remains difficult.…”
Section: Discussionmentioning
confidence: 99%